Getting What You Came For: The Smart Student's Guide to Earning an M.A. or a Ph.D. - Peters, Robert L. (New York Farrar, Straus and Giroux, 1997)
Is graduate school right for you? Should you get a master?s or a Ph.D.? How can you choose the best possible school? This classic guide helps students answer these vital questions and much more. It will also help graduate students finish in less time, for less money, and with less trouble. Based on interviews with career counselors, graduate students, and professors, Getting What You Came For is packed with real-life experiences. It has all the advice a student will need not only to survive but to thrive in graduate school, including: instructions on applying to school and for financial aid; how to excel on qualifying exams; how to manage academic politics?including hostile professors; and how to write and defend a top-notch thesis. Most important, it shows you how to land a job when you graduate.